2023
DOI: 10.1111/srt.13285
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in the role of Yes‐associated protein in dermatosis

Abstract: Background: Dermatosis is a general term for diseases of the skin and skin appendages including scleroderma, psoriasis, bullous disease, atopic dermatitis, basal cell carcinoma, squamous cell carcinoma, and melanoma. These diseases affect millions of individuals globally and are a serious public health concern. However, the pathogenesis of skin diseases is not fully understood, and treatments are not optimal. Yes-associated protein (YAP) is a transcriptional coactivator that plays a role in the regulation of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 94 publications
0
5
0
Order By: Relevance
“…This finding highlights the role of fibroblasts in the mechanical process of pathological melanoma cell proliferation, beyond the known keratinocyte-melanocyte crosstalk, and suggests their contribution to cancer development. Additionally, if epidermal stem cells are deficient in the inhibitor of plexin-B, the inhibition of YAP would be compromised, resulting in the cells' inability to sense mechanical pressure, which further disinhibits YAP [72]. This disinhibition can lead to cellular proliferation, potentially contributing to the development of basal cell carcinoma (BCC) [72].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding highlights the role of fibroblasts in the mechanical process of pathological melanoma cell proliferation, beyond the known keratinocyte-melanocyte crosstalk, and suggests their contribution to cancer development. Additionally, if epidermal stem cells are deficient in the inhibitor of plexin-B, the inhibition of YAP would be compromised, resulting in the cells' inability to sense mechanical pressure, which further disinhibits YAP [72]. This disinhibition can lead to cellular proliferation, potentially contributing to the development of basal cell carcinoma (BCC) [72].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, if epidermal stem cells are deficient in the inhibitor of plexin-B, the inhibition of YAP would be compromised, resulting in the cells' inability to sense mechanical pressure, which further disinhibits YAP [72]. This disinhibition can lead to cellular proliferation, potentially contributing to the development of basal cell carcinoma (BCC) [72]. In an in vitro study utilizing spiny mice (Acomys cahirinus) applied to human fibroblasts, treatment with verteporfin, a nuclear YAP-TEAD inhibitor, led to persistent enhancement of myofibroblast differentiation mediated by TGF-β, resulting in tissue fibrosis rather than regeneration; conversely, forcibly increasing YAP activity might prevent and rescue this process [73].…”
Section: Discussionmentioning
confidence: 99%
“…Current studies have shown that TAZ is involved in the occurrence and development of a variety of neoplastic diseases 4 . In addition, TAZ is also related to the maintenance of inflammatory diseases 5–8 . However, its role and molecular mechanisms in lichen planus remain to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“… 4 In addition, TAZ is also related to the maintenance of inflammatory diseases. 5 , 6 , 7 , 8 However, its role and molecular mechanisms in lichen planus remain to be elucidated. Herein, we preliminarily explained the expression of TAZ in lichen planus, and analyzed the correlation between TAZ expression and the clinical features of lichen planus patients to explore the possible mechanism of TAZ in the occurrence and development of lichen planus.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the mechanism of scar formation has been reported to be the persistent activation of Yes-associated protein (YAP) that up-regulates fibrosis and leads to excessive ECM deposition [ 7 , 8 ]. Thus, YAP inhibition could represent a therapeutic strategy to suppress fibrosis in the treatment of various fibrosis diseases [ 9 , 10 ]. Verteporfin (VP), a Food and Drug Administration (FDA) approved porphyrin compound, has confirmed to inhibit YAP expression, suppress fibrosis and yield scarless skin regeneration [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%